Religious Research Model (Fiqh, Philosophy, Islamic Thought, History) - Lia Nur ‘Aini; Cepty Afifah Ranti (al-Afkar, Journal For Islamic Studies, 2025)
This paper aims to examine religious research models (Fiqh, Philosophy, Islamic Thought, History) in Islamic studies methodology. This article is the result of a study from bibliographic research with data sources in the form of books, articles and writings relating to Islamic study methodology, religious research models, especially Fiqh, Philosophy, Islamic Thought, History. The data obtained was then processed using the content analysis method (contect analysis). This research method is qualitative using descriptive-analytical methods. The results of this research are that along with the dynamics of culture in people's lives and problems become increasingly complex, religious research models such as fiqh, philosophy, Islamic thought and history are important to study to answer every problem of life and cultural practices that are developing in society without being separated from the substance of religion. Islam.